2019
DOI: 10.3329/jsr.v11i2.38797
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Natural Convection Flow in a Hexagonal Enclosure Having Vertical Fin

Abstract: Numerical study of natural convection flow in a hexagonal enclosure with a single vertical fin attached to its heated bottom wall has been carried out. Finite element method based Galerkin weighted residual technique is used to solve the governing equation. The horizontal walls of the enclosure are kept at constant high temperature while the inclined walls are kept at constant cold temperature. A vertical heated fin is attached to the hot bottom wall with a length  at a position  from the left surface having t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…They observed that the effect of fin location on the rate of heat transfer was depended on strongly affected by Rayleigh number, and the fin length. Asad et al [5] explored numerically investigation of natural convection flow in a hexagonal enclosure having vertical fin. They conclude that the rate of heat transfer enhanced for greater Rayleigh number when fin length is kept constant.…”
Section: A Amplitudementioning
confidence: 99%
“…They observed that the effect of fin location on the rate of heat transfer was depended on strongly affected by Rayleigh number, and the fin length. Asad et al [5] explored numerically investigation of natural convection flow in a hexagonal enclosure having vertical fin. They conclude that the rate of heat transfer enhanced for greater Rayleigh number when fin length is kept constant.…”
Section: A Amplitudementioning
confidence: 99%
“…Reports on the natural convective flow of a nanofluid in square cavities incorporated with fins abound in literature, see references 20–27 . The influence of fins on mixed convective flow in a wavy‐wall enclosure containing nanofluid was detailed in conducted by Fayz‐Al‐Asad and colleagues 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…By exploring the literature records, it was noticed that more activities relevant to the instant study are found in [30][31][32]. Recently, Fin related papers for different shape of enclosure are studied by Asad et al [33][34][35]. Also, numerous investigations have been conveyed about non-linear PDE equations, which can be viewed [36][37][38].…”
Section: Introductionmentioning
confidence: 99%